Investigation of corrosion inhibition properties of caffeine on nickel by electrochemical techniques - Ebadi, M.; Mahmoudian, M.R.; Leng, S.Y.; Basirun, Wan Jefrey (Electrochemical Science Group, 2012)
The corrosion behaviour of Ni surface in the absence and presence of caffeine in 3.5% NaCl solution is studied using electrochemical impedance spectroscopy, open circuit potential, electrochemical noise analysis and linear scan voltammetry. The corrosion rate of the nickel surface decreases and the inhibition efficiency increases from 93.7% to 96.8% with the increase of caffeine in the corrosive solution. The FESEM images show that the caffeine addition in the corrosive solution reduces the formation of pits and cavities on the nickel surface.